Peran Penting Character Building dalam Membentuk Kepribadian Mahasiswa PGMI sebagai Calon Guru Profesional Beretika - restella, rika; Eva Faridah; Edy Surya (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
Character is a treatment that shows the good and bad of that person. As a candidate to educate mush have agood character within. Educators are a big component in educating the character of a person or student. Future educators have very big challenges different from today because the times are growing and technology is getting more sophisticated. The purpose of this research is to provide learning for prospective educators such as PGMI students in implementing character. The method used is qualitative, namely by using library research by collecting various data and then collaborating on the information obtained. The results of this study discuss the implementation of the character that must exist in PGMI students to build teacher professionalism in.